2016
DOI: 10.1016/j.jped.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Atypical manifestations of Epstein–Barr virus in children: a diagnostic challenge

Abstract: Physicians should be cautious about uncommon presentations of the viral infection and consider EBV as a causative agent when they encounter similar clinical pictures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 41 publications
0
31
0
4
Order By: Relevance
“…A thorough research of the literature showed that although rare, Epstein-Barr virus (EBV) can also be linked to FNP [3,4] . Here we present the case of two brothers with an EBV-derived unilateral FNP.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough research of the literature showed that although rare, Epstein-Barr virus (EBV) can also be linked to FNP [3,4] . Here we present the case of two brothers with an EBV-derived unilateral FNP.…”
Section: Introductionmentioning
confidence: 99%
“…Dermatitis can be macular, erythematous, petechial, scarlatiniform, urticarial, herpertiform or similar to erythema multiforme, mainly involving the upper limbs and the trunk, and is observed in 5% of patients (9,10). The symptoms are well tolerated and have a low frequency of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Primary infection with EBV is more frequent during childhood and causes a mild disease. The disease is typically asymptomatic in 20%-80% of individuals by the age of two-to-three years [1,3]. When uninfected teenagers and young adults are exposed to EBV, approximately 30%-70% will develop infectious mononucleosis (IM) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Following EBV's infection of B cells, a specific set of latency-related genes and transcripts are expressed, and the virus could remain dormant in resting memory B cells, from which it intermittently reactivates at any mucosal site where B cells are present (Table 1) [4,5]. The reactivation of EBV poses a great and difficult challenge to infected hosts [3]. In healthy adults, it is estimated that for every million B cells in circulation, approximately 1 to 50 are infected with EBV, with the number of latently-infected cells in each individual remaining stable for several years [6].…”
mentioning
confidence: 99%